2011
DOI: 10.1002/app.34555
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of rod‐coil molecules into lateral chain‐length‐dependent supramolecular organization

Abstract: In this article, we report synthesis and characterization of the self-assembly behavior of coilrod-coil molecules, consisting of four biphenyls and a pterphenyl unit linked together with ether bonds as a rod segment. These molecules contain lateral methyl or ethoxymethyl groups at 2 and 5 positions of the middle benzene ring of p-terphenyl. The self-assembling behavior of these materials was investigated by means of DSC, POM, and SAXS in the bulk state. The results reveal that selfassembling behavior of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…It should be pointed out that we reported previously that the lateral alkyl groups grafted on the center of the rod segment significantly to influence the self‐assembling behavior of rod–coil molecules. Recently, we have constructed the hexagonal‐perforate lamellar, columnar, body‐centered tetragonal, and hexagonal closed‐packed nanostructures with various lattice constants, by synthesizing rod–coil molecules containing lateral alkyl groups in the center of rod segments …”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out that we reported previously that the lateral alkyl groups grafted on the center of the rod segment significantly to influence the self‐assembling behavior of rod–coil molecules. Recently, we have constructed the hexagonal‐perforate lamellar, columnar, body‐centered tetragonal, and hexagonal closed‐packed nanostructures with various lattice constants, by synthesizing rod–coil molecules containing lateral alkyl groups in the center of rod segments …”
Section: Resultsmentioning
confidence: 99%
“…4,4′‐Biphenol, poly(ethylene glycol) methyl ether (molecular weight = 350, 550, 750 g mol −1 ), toluene‐ p ‐sulfonyl chloride (99%), pyridine, potassium carbonate, methyl‐2,5‐dihydroxybenzoate, dimethylbiphenyl‐4,4′‐dicarboxylate, triethylamine (99.5%), 18‐crown‐6 (99%) and conventional reagents were used as received. Compounds 3a–3c were prepared according to similar procedures described elsewhere (see supporting information) …”
Section: Methodsmentioning
confidence: 99%
“…Lee and co‐workers have shown that rod–coil molecules incorporating lateral methyl groups in the middle of the rod segments spontaneously organise into hexagonal nanostructures in the liquid crystalline phase . More recently, the self‐assembling behaviour of coil–rod–coil molecules incorporating lateral methyl or ethyl groups in the centre of the rod‐like building block, and poly(ethylene oxide) with a degree of polymerisation of 7, 12 and 17 as coil segments, has been reported . The results reveal that lateral alkyl groups incorporated in rod building blocks lead to loose‐packing molecules, and govern the creation of 3‐D nano‐assemblies in the bulk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various supramolecular nano-structures can be formed by self-assembly of rod building block copolymers, which have a strong capacity to self-organize into a variety of ordered nanostructures, through tuning non-covalent driving forces of rod-coil block copolymers, such as interactions of pi-pi stacking, hydrophilic and hydrophobic effects, electrostatic interaction, and so on [13][14][15][16][17][18][19][20][21]. Lee and other research groups reported that rod-coil molecules are able to self organize into unique self-assembling nanostructures, such as 1-D lamellar, 2-D columnar, cylinders, discrete bundles, ribbons, and vesicles [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%